An integrated approach of Analytic Hierarchy Process and Fuzzy Linear Programming for supplier selection. (28th July 2008) - Kumar, Pravin; Shankar, Ravi; Yadav, Surendra S.
Supplier selection is a Multi-Criteria Decision-Making problem in a supply chain involving many qualitative and quantitative factors. In this paper, an integrated approach using Analytic Hierarchy Process (AHP) and Fuzzy Linear Programming (FLP) is adopted for supplier selection and quota allocation problem. AHP is used to rate the suppliers, while FLP is used to allocate the quota to the suppliers. In FLP, multiple conflicting objectives with some constraints of buyers and suppliers are considered to optimise the order quantities. The ratings of suppliers, which are outputs of AHP, are used as inputs for Total Value of Purchase (TVP) where TVP is one of the objectives of FLP. Finally, sensitivity of the method has been analysed to understand the effect of variation in priority of selection criteria on suppliers' rating and then on quota allocation.